GREEN HUMAN RESOURCE MANAGEMENT: NURTURING SUSTAINABILITY IN THE WORKPLACE (International Journal of Food and Nutritional Sciences, 2022)
Green HRM is the application of HRM policies to support the cause of environmental sustainability and, more broadly, the sustainable use of resources within business organizations. The study's goals are to investigate how green HRM practices are implemented in businesses and to advance the philosophy that's necessary for correctly coordinating HRM practices with green HRM goals within an enterprise. This descriptive approach uses data from primary and secondary sources. Green HRM includes all initiatives meant to assist a company in implementing its environmental management plan and lowering its carbon footprint. These initiatives include hiring and onboarding new employees, managing performance reviews and incentives, providing training and development, and handling pay and benefits.